(untitled) ("Journal "U". Economy. Management. Finance.", 2026)
The article examines the impact of digital infrastructure on entrepreneurship development in the Republic of Bashkortostan and neighbouring regions. It identifies existing disproportions affecting entrepreneurship in the era of digitalisation and proposes measures to reduce them.